Malignant STK11 adnexal tumor harboring a somatic mutation in a woman previously diagnosed with mesothelioma, a case report - Christina R. Rutherford; Taylor A. Rives; Dava W. Piecoro; Charles S. Dietrich (Gynecologic Oncology Reports)
STK11 germline pathogenic variants are typically associated with Peutz-Jeghers syndrome, an autosomal dominant disease characterized by hamartomatous polyps in the gastrointestinal tract, hyperpigmented patches, and increased risk of stomach, colorectal, small bowel, and breast cancers (Beggs et al., 2010). Mutations in this gene have also been identified in skin, pancreatic, testicular, and stromal ovarian cancer (Fagerberg et al., 2014). To date, there have been less than 30 cases of ovarian cancer reported associated with mutated STK11 (Bennett et al., 2021). In this report, we discuss a rare case of a STK11 adnexal tumor in a 39-year-old woman previously diagnosed with malignant mesothelioma. After 33 months with no evidence of disease following cytoreductive surgery with HIPEC and adjuvant chemotherapy, a new retroperitoneal lesion was noted on imaging. After resection, molecular testing indicated an STK11 mutation, and histology was consistent with an STK11 adnexal tumor. A high index of suspicion is required to make the diagnosis of STK11 adnexal tumor due to its non-distinct pathology and IHC staining. Due to the rarity of this neoplasm, analysis of current and future cases of the STK11 adnexal tumor is necessary to understand its pathogenesis, genetic mutational analysis, clinical course, and best treatment options.